O relacionamento professor-aluno e o bullying no ensino fundamental - Passos, Virgínia de Oliveira Alves (2012)
The social context is marked by countless situations identified by violence. The school as a place for developing individuals is a setting for conflicts. A phenomenon of intense violence, is worrying educators in general - bullying - term used to refer to aggressive attitudes, intentional, repetitive, adopted by one or more students against another(s), causing pain, distress and suffering. Insults, intimidation, nicknames, teasing, accusations, often leading to exclusion, and physical, psychological, moral and material. The overall goal of this research is to investigate the role of the teacher-student relationship in the occurrence of conflict situations involving students, from the students' perspective. The study included 124 students in 7th grade from three elementary schools in Recife (PE). Students were asked to write an essay about "School Violence", and then completed a questionnaire about the relationship with colleagues and two teachers - with Good Relationships and with Difficult Relationship. A thematic analysis of newsrooms shows that the majority of students referred directly to bullying to speak about school violence. This practice was also addressed indirectly, without making explicit reference to the term bullying. Some students expressed their targets / victims of bullying, and others claimed to have witnessed such a practice. Analysis of the questionnaires showed the forms of involvement in bullying and aspects of the teacher-student relationship. Statistical analysis showed correlational link between student authors / aggressors and negative aspects of the relationship with teachers. The results allow for greater understanding of the influence of interpersonal relationships in the school context.